The qualities of dyed YAG:Ce3+@SiO2 for WLEDs via energy conversion - Phung Ton That; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
Y3Al5O12:Ce3+ (YAG:Ce3+), the most common yellow phosphor for WLEDs, has a red insufficiency in its light spectrum. The Ce3+ spectral profile is modified in this research using surface-located ATTO-Rho101 dye molecules, which have powerful, wide impregnation in the greenish-yellow spectroscopic zone of Ce3+ radiation and vivid red-emitting radiation. To create a spherical shell and evenly dispersed micro and nanometer YAG:Ce3+, a modified solvothermal technique is applied. Surface SiO2 covering and synchronized dye embedding are accomplished using solvothermally generated YAG:Ce3+, temperature-stimulated micro-YAG:Ce3+, plus commercialized phosphorus. Upon blue light excitation, the accumulated YAG:Ce3+@SiO2+dye powder exhibits efficient radiative conversion/reintake from Ce3+ within the internal structure of YAG to the pigment particles from the SiO2 external shell, despite the phosphors' diameter; which likely boosts its red radiation. Fluorescence microscopy would be a suitable way to determine the reabsorption of powdered substances.